2020
DOI: 10.3390/insects11110767
|View full text |Cite
|
Sign up to set email alerts
|

Gene Characterization and Enzymatic Activities Related to Trehalose Metabolism of In Vitro Reared Trichogramma dendrolimi Matsumura (Hymenoptera: Trichogrammatidae) under Sustained Cold Stress

Xin Lü,
Shi-chou Han,
Zhi-gang Li
et al.

Abstract: Trichogramma spp. is an important egg parasitoid wasp for biocontrol of agriculture and forestry insect pests. Trehalose serves as an energy source or stress protectant for insects. To study the potential role of trehalose in cold resistance on an egg parasitoid, cDNA for trehalose-6-phosphate synthase (TPS) and soluble trehalase (TRE) from Trichogramma dendrolimi were cloned and characterized. Gene expressions and enzyme activities of TdTPS and TdTRE were determined in larvae, prepupae, pupae, and adults at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
0
9
0
1
Order By: Relevance
“…The other two hsp genes found to be overexpressed in the natural populations compared with Ngoussou were hsp90_beta and hsp70 1/8. Trehalose (synthesized by TPS 1/2) contribute to the maintenance of warm temperature, a condition needed for survival of Anopheles [43,70] and is known to promote longevity, fecundity and cold tolerance in insects [46]. TPS 1/2 was also found to be overexpressed in heat-hardened, unexposed, and permethrin-resistant females, compared with Ngoussou, with the highest expression in heat-hardened females.…”
Section: Common Metabolic Resistance Genes Are Associated With Thermomentioning
confidence: 97%
See 1 more Smart Citation
“…The other two hsp genes found to be overexpressed in the natural populations compared with Ngoussou were hsp90_beta and hsp70 1/8. Trehalose (synthesized by TPS 1/2) contribute to the maintenance of warm temperature, a condition needed for survival of Anopheles [43,70] and is known to promote longevity, fecundity and cold tolerance in insects [46]. TPS 1/2 was also found to be overexpressed in heat-hardened, unexposed, and permethrin-resistant females, compared with Ngoussou, with the highest expression in heat-hardened females.…”
Section: Common Metabolic Resistance Genes Are Associated With Thermomentioning
confidence: 97%
“…To investigate the potential role of pleiotropic genes on thermotolerance and insecticide resistance, 3-4 day-old females which survived exposure at 44°C for 30min (and allowed to rest for 12h), those which survived exposure to 0.75% permethrin and unexposed females were used for qRT-PCR, targeting 9 genes previously associated with thermotolerance and/or insecticide resistance [20,31,[43][44][45][46]. These include 6 heat shock proteins: [hsp90 molecular chaperone HtpG (AGAP006959), hsp90 beta (AGAP001424), hsp83 (AGAP006958), hsp70 1/8 (AGAP004944), hsp90 ATPase activator (AGAP010514) and hsp70 (AGAP004581)]; trehalose-6-phosphate synthase/phosphatase (TPS 1/2, AGAP008227), and 2 ionotropic receptor genes, IR21a (AGAP008511) and IR25a (AGAP010272).…”
Section: Transcriptional Profiling Of Thermotolerance-related Genes Umentioning
confidence: 99%
“…Trehalose (synthesized by TPS 1/2) contribute to the maintenance of warm temperature, a condition needed for survival of Anopheles [46,71] and is known to promote longevity, fecundity and cold tolerance in insects [49], as well as stabilizing proteins during thermal stress [72]. TPS 1/2 was also found to be overexpressed in heat-hardened, unexposed, and permethrin-resistant females, compared with Ngoussou, with the highest expression in heat-hardened females.…”
Section: Common Metabolic Resistance Genes Are Associated With Thermotolerance and Permethrin Resistancementioning
confidence: 99%
“…To investigate the potential role of pleiotropic genes on thermotolerance and insecticide resistance, 3-4 day-old females [40] which survived 44 • C exposure for 1 h (and allowed to rest for 2 h [45]), those which survived exposure to 0.75% permethrin and unexposed females were used for qRT-PCR, targeting 9 genes previously associated with thermotolerance and/or insecticide resistance [20,31,[46][47][48][49]. These include 6 heat shock protein genes: [hsp90 molecular chaperone HtpG (AGAP006959), hsp90 beta (AGAP001424), hsp83 (AGAP006958), hsp70 1/8 (AGAP004944), hsp90 ATPase activator (AGAP010514) and hsp70 (AGAP004581)]; the trehalose-6-phosphate synthase/phosphatase (TPS 1/2, AGAP008227), and the 2 ionotropic receptor genes, IR21a (AGAP008511) and IR25a (AGAP010272).…”
Section: Transcriptional Profiling Of Thermotolerance-related Genes Using Qrt-pcrmentioning
confidence: 99%
“…They further determined the optimum cold storage conditions at a temperature of 13 • C for 10 or 15 d for late-age pupae of this parasitoid. Separately, Lü et al [7] demonstrated that a temperature of 13 • C was the cold tolerance threshold temperature and the prepupal stage was a critical developmental period for in vitro rearing of another parasitoid Trichogramma dendrolimi Matsumura, an important biological control agent of biological control programs.…”
mentioning
confidence: 99%